2018
DOI: 10.1371/journal.pone.0192670
|View full text |Cite
|
Sign up to set email alerts
|

Association between periconceptional weight loss and maternal and neonatal outcomes in obese infertile women

Abstract: BackgroundObesity in women of reproductive age has deleterious effects on reproductive and offspring health. In this study, we aimed to evaluate the association between the magnitude of periconceptional body-mass index (BMI) change and maternal and neonatal outcomes in obese infertile women who participated in the LIFEstyle study. The LIFEstyle study was a randomized controlled trial, evaluating if a six-month lifestyle intervention program prior to infertility treatment in obese infertile women improved birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
2
18
0
2
Order By: Relevance
“…One study in obese women found that interpregnancy weight loss beyond returning to pre-pregnancy weight was associated with a decreased risk of gestational diabetes in a second pregnancy [24]. Preconception weight loss may be beneficial for decreasing risk of preterm birth, however, the impacts of preconception weight loss on other birth outcomes and offspring health have yet to be fully elucidated [25,26]. Depending on preconception diet quality, preconception weight loss may affect mothers' nutritional status and, therefore, birth outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
“…One study in obese women found that interpregnancy weight loss beyond returning to pre-pregnancy weight was associated with a decreased risk of gestational diabetes in a second pregnancy [24]. Preconception weight loss may be beneficial for decreasing risk of preterm birth, however, the impacts of preconception weight loss on other birth outcomes and offspring health have yet to be fully elucidated [25,26]. Depending on preconception diet quality, preconception weight loss may affect mothers' nutritional status and, therefore, birth outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention effects on weight at conception were unreported for the 27% of women who conceived after the index cycle [49]. The LIFEstyle trial in the Netherlands did not prospectively assess weight during the 18 months of fertility treatments that followed the 6 month intervention [42] but did report that maternal weights available at 8-12 weeks' gestation for 244 women (76% of the 321 who conceived) were significantly reduced from baseline for intervention participants (−4.1 kg vs −1.0 kg for intervention vs control participants) [50]. Given the likelihood of weight regain following lifestyle interventions [51], it is important that studies of preconception interventions include frequent assessments to accurately capture maternal weight at conception.…”
Section: Summary Of Preconception Interventionsmentioning
confidence: 99%
“…When limited weight gain during pregnancy was advised to obese mothers to improve these outcomes, there were only small effects on foetal growth and metabolic outcomes [22,23]. A preconceptional weight loss (WL) is now widely recommended to obese women, improves fertility and reduces the occurrence of metabolic complications [24]. However, whereas some studies demonstrate a positive impact [25,26,27,28], other studies indicate potential deleterious effects [28,29,30].…”
Section: Introductionmentioning
confidence: 99%